Taking the S out of ERISA: How the Security of Retirement Accounts May Change in the Face of Recent Supreme Court and Circuit Court Decisions - Kyle R. Cox (Washington University Journal of Law and Policy, 2026)
The Employee Retirement Income Security Act of 1974 (ERISA) is the statutory framework that protects the retirement funds of millions of employees across the country, applying strict fiduciary liabilities against those with access to plan funds and instituting enforcement provisions. Employers have imposed mandatory arbitration clauses on claims that arise out of ERISA, seemingly in direct conflict with ERISA’s promise of “ready access to the Federal courts.” Although the Supreme Court has been silent on the enforceability of these clauses, it has weighed in on the enforceability of similar clauses within other contexts in Epic Systems v. Lewis and Lamps Plus v. Varela. Circuit courts have also begun to re-affirm employees’ rights back with the Effective Vindication Doctrine, ensuring that mandatory arbitration clauses do not block the exercise of an employee’s federal statutory right. This Comment analyzes the Supreme Court’s precedent in Epic Systems and Lamps Plus, highlighting the Court’s continued favor of arbitration clauses. Although the cases do not mandate the enforcement of arbitration clauses under ERISA, they do signal the Court’s likelihood to enforce such agreements. This Comment also delves into the viability of the Effective Vindication Doctrine to limit the scope of arbitration agreements under ERISA, finding that the doctrine is a tool that could challenge the enforceability of arbitration agreements in limited circumstances—but that it is unlikely to be a saving grace for most plan participants. For the foreseeable future, employees are unlikely to have the “access to the Federal courts” that they were promised, and decisions regarding plan funds will continue to lay at the mercy of arbitrators.
Keywords: #ERISA; #MandatoryArbitration; #AccessToFederalCourts; #EffectiveVindicationDoctrine; #RetirementProtection; #EmployeeRights; #ArbitrationPrecedent; #PlanParticipantRights; #ERISAEnforcement; #LaborAndEmploymentLaw